2019
DOI: 10.4269/ajtmh.18-0788
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphism and Dissemination of Histoplasma capsulatum in the Upper Respiratory Tract after Intranasal Infection of Bats and Mice with Mycelial Propagules

Abstract: . This article describes, for the first time, the role of the nasal mucosa (NM) as the initial site for the Histoplasma capsulatum mycelial-to-yeast transition. The results highlight that yeasts may arrive to the cervical lymph nodes (CLN) via phagocytes. Bats and mice were intranasally infected with H. capsulatum mycelial propagules and they were killed 10, 20, and 40 minutes and 1, 2, and 3 hours after infection. The NM and the CLN were monitored for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 35 publications
(42 reference statements)
2
12
0
1
Order By: Relevance
“…Bats are able to develop natural and experimental histoplasmosis infections [ 1 , 2 , 3 , 4 , 5 , 6 ]. Infected bats could act as reservoirs and dispersers of H. capsulatum in favorable environments, playing a possible role in the incorporation of the fungus in new ecological niches [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bats are able to develop natural and experimental histoplasmosis infections [ 1 , 2 , 3 , 4 , 5 , 6 ]. Infected bats could act as reservoirs and dispersers of H. capsulatum in favorable environments, playing a possible role in the incorporation of the fungus in new ecological niches [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, by utilizing this innovative genetic approach and by simulating a natural host infection, these authors found relevant data, which undoubtedly demonstrated that infective Histoplasma M-phase propagules spent 2-3 h to convert in the parasitic Y-phase. Furthermore, they also demonstrated that this fungus can also utilize other extrapulmonary sites to initiate its M-to-Y transition, where the link between innate and adaptive immune responses occurs, such as the mucosal-associated lymphoid tissues in the upper respiratory tract [8].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have processed the infective M-phase to explore the immune responses triggered by the host to this particular fungal morphotype, in the clinical evolution of histoplasmosis. New information regarding different sites and the time spent for the in vivo H. capsulatum M-to-Y transition was reported by Suárez-Álvarez et al [8]. They detected the expression of phase-specific genes for M-and Y-phases using RT-PCR assays in tissue samples taken from the upper respiratory tract of infected mice.…”
Section: Introductionmentioning
confidence: 99%
“…Conidia and small hyphal fragments of the H. capsulatum mycelial phase constitute the major aerosolized infectious propagules found in the environment, which can be inhaled by susceptible hosts. Once in the host’s respiratory compartments are at 37 °C, the mycelial propagules convert to the parasitic yeast phase in approximately 1–3 h [ 6 ]. This facilitates an infection that can lead to a localized pulmonary disease or to a disseminated disease.…”
Section: Introductionmentioning
confidence: 99%